2016
DOI: 10.3389/fnagi.2016.00139
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging to Detect Early Molecular and Cellular Changes in Alzheimer's Disease

Abstract: Recent pharmaceutical trials have demonstrated that slowing or reversing pathology in Alzheimer's disease is likely to be possible only in the earliest stages of disease, perhaps even before significant symptoms develop. Pathology in Alzheimer's disease accumulates for well over a decade before symptoms are detected giving a large potential window of opportunity for intervention. It is therefore important that imaging techniques detect subtle changes in brain tissue before significant macroscopic brain atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 111 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…AGuIX nanoparticles have a hydrodynamic diameter smaller than 5 nm and have been already efficiently used for MRI imaging and radio-sensitization [ 110 ]. Free ligands are available at the surface of AGuIX and can be used to chelate radioisotopes (e.g., 68 Ga 3+ or 111 In 3+ ) in order to perform PET or Single-photon emission computed tomography (SPECT) imaging [ 111 , 112 ]. Moreover, the covalent grafting of a near-infrared dye, such as cyanine5.5 (Cy5.5), is also achievable for optical imaging [ 113 ].…”
Section: Mnps As In Vivo Diagnostic Probesmentioning
confidence: 99%
“…AGuIX nanoparticles have a hydrodynamic diameter smaller than 5 nm and have been already efficiently used for MRI imaging and radio-sensitization [ 110 ]. Free ligands are available at the surface of AGuIX and can be used to chelate radioisotopes (e.g., 68 Ga 3+ or 111 In 3+ ) in order to perform PET or Single-photon emission computed tomography (SPECT) imaging [ 111 , 112 ]. Moreover, the covalent grafting of a near-infrared dye, such as cyanine5.5 (Cy5.5), is also achievable for optical imaging [ 113 ].…”
Section: Mnps As In Vivo Diagnostic Probesmentioning
confidence: 99%
“…Recent pharmaceutical trials have demonstrated that slowing or reversing pathology in Alzheimer's disease (AD) is likely to be possible only in the earliest stages of disease, perhaps even before significant symptoms develop [1]. The development and use of diagnostic tools for the early detection of AD, therefore, might be helpful for clinicians.…”
Section: Alzheimer's Disease and Mild Cognitive Impairmentmentioning
confidence: 99%
“…Imaging biomarkers of neurodegeneration include [ 18 F]fluorodeoxyglucose positron emission tomography ([ 18 F]FDG-PET) 1 , 2 and magnetic resonance imaging (MRI) hippocampal volume measures. 3 Although both of these biomarkers are nonspecific to Alzheimer’s disease (AD), they can provide evidence about its severity due to neuronal damages. It is known that pathological phenomena that lead to synaptic dysfunction affect metabolism before cell death and detectable atrophy.…”
Section: Introductionmentioning
confidence: 99%